Knowledge and Attitude Regarding Attention Deficit Hyperactivity Disorder among School Teachers in Kathmandu Metropolitan City, Nepal - Bhele, Rajyashwaree; Gurung, Shreejana (NPRC Journal of Multidisciplinary Research, 2025)
Background: Attention Deficit Hyperactivity Disorder (ADHD) is a prevalent neurodevelopmental disorder impacting children's academic and social development. Teachers play a critical role in early identification and support. This study assessed the knowledge and attitudes regarding ADHD among school teachers in Kathmandu Metropolitan City.Methods: A descriptive cross-sectional study was conducted among 105 teachers from three purposively selected schools (Arunima Higher Secondary School, Xavier International School, and Mahan Siddhartha School). A total enumerative sampling technique was used. Data were collected using a semi-structured, self-administered questionnaire comprising three parts: socio-demographic information, a 10-item knowledge assessment, and a 5-point Likert scale for attitude. Data were analyzed using descriptive statistics (frequency, percentage, mean, standard deviation) and inferential statistics (Chi-square test) with SPSS.Results: The study revealed that more than half of the teachers (54.29%) had fair knowledge, while 41.9% had poor knowledge, and only a small minority (3.8%) had good knowledge regarding ADHD. In contrast, the vast majority (88.57%) held a favorable attitude towards children with ADHD. No statistically significant association was found between knowledge levels and socio-demographic variables such as age, sex, education, teaching experience, or prior awareness of ADHD (p > 0.05). Furthermore, there was no significant association between overall knowledge and attitude scores (p = 0.223).Conclusion: Despite holding largely favorable attitudes, school teachers in Kathmandu Metropolitan City possess insufficient knowledge about ADHD. This knowledge-practice gap highlights an urgent need for structured training and awareness programs to equip teachers with the necessary skills to effectively identify, manage, and support students with ADHD in the classroom.